2015
DOI: 10.1113/jp270078
|View full text |Cite
|
Sign up to set email alerts
|

Sir Joseph Barcroft: one victorian physiologist's contributions to a half century of discovery

Abstract: During the first half of the 20th Century, Joseph Barcroft, KBE, FRS of Cambridge University became a world leader in respiratory physiology. He determined the role of neural stimulation in the oxygen consumption of several organs, established many of the factors that regulate the binding of oxygen to haemoglobin, explored the determinants of a human's acclimatization to high altitude and developed the field of fetal cardiovascular physiology. Chair of the Cambridge Department of Physiology from 1925 to 1937, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…14 It was shown that evolution has given the lungs, blood, and placenta of a pregnant woman and the brain of a fetal an adaptation to hypoxia. [13][14][15][16][17] However, there is no mention of a functional test for fetal resistance to acute intrauterine hypoxia. 14,16,17 Official obstetrics and gynecology do not have a standard functional test to assess the reserves of adaptation of the fetus to intrauterine hypoxia before delivery.…”
Section: Resultsmentioning
confidence: 99%
“…14 It was shown that evolution has given the lungs, blood, and placenta of a pregnant woman and the brain of a fetal an adaptation to hypoxia. [13][14][15][16][17] However, there is no mention of a functional test for fetal resistance to acute intrauterine hypoxia. 14,16,17 Official obstetrics and gynecology do not have a standard functional test to assess the reserves of adaptation of the fetus to intrauterine hypoxia before delivery.…”
Section: Resultsmentioning
confidence: 99%
“…Less Death from COVID-19 at High Altitude legacy of the colonialist mentality of the 20th century [28][29][30] , and must be radically changed in the minds of new physicians and researchers; highaltitude physiology is a heritage of biological richness that hides key secrets for understanding life and discovering new cures. Our work is a wonderful example of the latter, where high-altitude hypoxia has been a key factor in protecting high-altitude populations from a pandemic that has been devastating worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Scientists and historians of science today usually locate the beginnings of fetal physiology—as a well-defined field with its research questions, methodology and animals—in the 1930s Cambridge, when Joseph Barcroft, after a successful career in adult respiratory and cardiovascular physiology, took his interest in oxygen absorption from adult to fetal bodies (Giussani et al, 2016 ; Longo, 2016 ; Buklijas, 2014 ). 3 Barcroft died in 1947, shortly after the publication of the foundational text of this new field, Researches on pre-natal life .…”
Section: Physiological Approaches To the Fetal Environmentmentioning
confidence: 99%